2023
DOI: 10.3390/insects14040386
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biogenic Amines in Social Insects: With a Special Focus on Ants

Abstract: Eusociality represents the higher degree of interaction in insects. This complex social structure is maintained through a multimodal communication system that allows colony members to be flexible in their responses, fulfilling the overall society’s needs. The colony plasticity is supposedly achieved by combining multiple biochemical pathways through the neuromodulation of molecules such as biogenic amines, but the mechanisms through which these regulatory compounds act are far from being fully disentangled. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Variation in biogenic amines levels have been identified as one of the leading causes of behavioral plasticity and specialization of social insects to different tasks (reviewed in ref. 132 ). Functional manipulation of biogenic amines has led to changes in behavior, dominance status and reproductive activity, as well as shifts in worker task performance 133 136 .…”
Section: Discussionmentioning
confidence: 99%
“…Variation in biogenic amines levels have been identified as one of the leading causes of behavioral plasticity and specialization of social insects to different tasks (reviewed in ref. 132 ). Functional manipulation of biogenic amines has led to changes in behavior, dominance status and reproductive activity, as well as shifts in worker task performance 133 136 .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic analyses showed the diversity and functions of DMs in S. invicta following exposure to cycloxaprid over different durations. These DMs are various fatty acids, nucleotides, hormones, and amines, which participate in numerous physiological processes, including lipid and energy metabolism, DNA synthesis, hormone signaling, neurotransmission, and overall metabolic activity ( Weyel and Wegener, 1996 ; Gäde et al, 2003 ; Kaczmarek and Boguś, 2021 ; Barbero et al, 2023 ). Correlation analysis showed that 226 DEGs exhibited significant correlations with 54 DMs (|R| > 0.8, p < 0.05), indicating the tight interplay between metabolites and genes in S. invicta treated with cycloxaprid.…”
Section: Discussionmentioning
confidence: 99%